ESSENTIAL FEATURES OF MODERN PARLIAMENTARISM - Surai I.H.; Honchar V.V. (Pressing Problems of Public Administration, 2016)
The article shows the understanding of the modern parliamentarism by a number of researchers. The article focuses on identifying and reasoning of the essential features of modern parliamentarism. It is proved that the main features of modern parliamentarism are the interaction of civil society and the state; the principle of representation; the supremacy of the parliament; democracy.